Comparative acceptability of beef and carabeef in processed corned beef - Chan, Frances C.
ABSTRACT Studies were conducted to develop a standardized formulation and process based on the Griffith Laboratory Research Department formulation for making corned beef and carabeef using available laboratory equipment. Comparative acceptability tests on corned beef and carabeef was also conducted. Following the developed formulation and process, corned beef was made using beef-brisket and cara-brisket. The products were evaluated objectively by means of cut-out, physico-chemical and microbiological tests. Results showed that a microbiologically safe and acceptable product could be produced even with the use of crude equipments. Taste panel evaluations by paired comparison and hedonic scale methods indicated that at the 5% level of significance, corned beef is more preferred than corned carabeef. A slight aftertaste was observed by the panel of judges in corned carabeef. Corned carabeef samples were darker in color (7.5 R 4/8.5) than corned beef samples (2.5 YR 5.5/6.5). In spite of these observations, the degree of acceptance seemed to indicate a good potential for using carabeef as raw material in corned beef.